Public relations and public service: police departments on Facebook - Livingstone, Randall M. (Policing and society, 2022)
Academic research on police departments’ use of social media has emerged over the past decade, often focusing on large, metropolitan police departments, from what they post, to how they interact with the public, to how they manage a social media presence during times of conflict such as riots. Largely missing from the research is empirical data on how police departments of various sizes employ communication strategies on social media. This research addresses this gap by analysing the use of Facebook by police departments of various sizes, from large cities to medium-sized suburbs and small rural towns in the Northeastern United States. Findings suggest that public relations-focused content is top-of-mind for departments of all sizes, though other content priorities vary, likely based on the size and nature of the community in which they operate. Additionally, the public uses a range of reaction options on posts, although the long-established Like reaction continues to be the most used.